أثر مشاركة المرأة بأعمال تربية الأغنام وبيع منتجاتها في تحسين العائد الاقتصادي للسكان الريفيين في منطقة المالكية التابعة لمحافظة الحسكة - سلوم, عفراء (Latakia University Journal -Biological Sciences Series, 2017)
يهدف البحث إلى تقدير أثر مشاركة المرأة بتربية الأغنام في تحسين العائد الاقتصادي للسكان الريفيين في منطقة المالكية (محافظة الحسكة)، من خلال تقدير العلاقة ما بين التابعين المتغيرين (العامل الأول: درجة مشاركة المرأة الريفية في أعمال تربية الأغنام وبيع منتجاتها)، و(العامل الثاني: وسطي الربح المحقق الناجم عن تربية الأغنام وبيع منتجاتها في منطقة الدراسة)، ومجموعة من العوامل المستقلة. جمعت البيانات من عينة عشوائية بلغ حجمها 152 امرأة ريفية من 30 قرية، واستخدم في تحليل البيانات بعض المقاييس الوصفية، والارتباط البسيط والمتعدد.بينت نتائج التحليل وجود علاقة ارتباط موجبة قوية ومعنوية احصائياً عند مستوى(1%) بين درجة مشاركة المرأة الريفية في تربية الأغنام وبيع منتجاتها، والمتغيرات المستقلة (عمر المبحوثة، حجم الأسرة، شراء وبيع الأغنام)، حيث بلغت قيمة معامل الارتباط المتعدد (r=0.920)، وقيمة معامل التحديد (r2=0.847)، أي أن العوامل المستقلة المذكورة تفسَر 84.7% من التغير في درجة مشاركة المرأة في أعمال تربية الأغنام وبيع منتجاتها، كما تبين وجود علاقة ارتباط موجبة قوية ومعنوية احصائياً عند مستوى(1%) بين متوسط الربح المحقق من بيع منتجات الأغنام، والمتغيرات المستقلة (عمر المبحوثة، وجود عمل إضافي للزوج، شراء وبيع الأغنام)، حيث بلغت قيمة معامل الارتباط المتعدد (r=0.931)، وقيمة معامل التحديد (r2=0.867)، أي أن العوامل المستقلة المذكورة تفسَر 86.7% من التغير في متوسط الربح المحقق من بيع منتجات الأغنام. The research aims to estimate the impact of the participation of women raising sheep in improving the economic return of the rural population in Maaliky area (Hasaka governorate), by selecting the relationship between followers variables (first factor: the degree of participation of rural women in the work of sheep breeding and selling its products), and (the second factor: the medial income arising from sheep breeding and selling its products in the study area), and a group of independent factors. Data were collected from a random sample size was 152 rural women from 30 villages of the area, used in the analysis of the data some descripted measures, simple and multiple Correlative, results of the analysis showed a correlation relationship strong positive and statistically significant at the level of(1%) between the degree of participation of rural women in sheep breeding and selling its products, with the independent variables (age of the surveyed, family size, and buying &selling sheep), while the value of multiple correlation were (r=0.920), and the value of the coefficient of determination were (r2 = 0.847), that is, the independent-mentioned factors explain 84.7% of the variation in the degree of participation of women in the work of sheep breeding and selling its products, also show a correlation relationship strong positive and statistically significant at the level of (1%)between the average realized gain from the sale of sheep products, and independent variables (age surveyed, there is additional work to her husband, and buying &selling sheep), while the value of multiple correlation were (r=0.931)as the value of the coefficient of determination( r2 = 0.867), that is independent factors mentioned explain 86.7% of the change in the average realized gain from the sale of sheep products.